2017
DOI: 10.4067/s0718-34292017005000016
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter accumulation and potato productivity with green manure

Abstract: Growth patterns and distribution of dry matter in different parts of potato plants (Solanum tuberosum, Solanaceae) with green manure can be positively influenced by the use of green manure. The aim was to evaluate the dry matter accumulation and productivity of potato with varying quantities of sunn hemp, Crotalaria juncea (Fabaceae) as a nitrogen source. The experiment used three different amounts of sunn hemp, equivalent to 100, 200 and 400 Kg ha -1 nitrogen (N), the recommended mineral N dose (250 Kg ha -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…1B), which demonstrated the effect of this treatment on the N accumulations in these organs. Mohamed et al (2017) found that the response to green manure was greater than that of mineral fertilizers, with higher N accumulations in potato at higher sun hemp doses, which were related to the rapid mineralization and N release of the green manure tissues (Watthier et al, 2020).…”
Section: Nitrogen (N)mentioning
confidence: 96%
See 1 more Smart Citation
“…1B), which demonstrated the effect of this treatment on the N accumulations in these organs. Mohamed et al (2017) found that the response to green manure was greater than that of mineral fertilizers, with higher N accumulations in potato at higher sun hemp doses, which were related to the rapid mineralization and N release of the green manure tissues (Watthier et al, 2020).…”
Section: Nitrogen (N)mentioning
confidence: 96%
“…Studies have reported increases in productivity and improvements in the quality of tubers from the use of BF applications when compared to the application of only chemical fertilizers for the Atlantic and Agata cultivars (Cardoso et al, 2015;Cardoso et al, 2017). Mohamed et al (2017) found that the productivity of potatoes was 24% greater with green manure than with mineral fertilization, which indicated the potential of alternative fertilizers to provide nitrogen for the growth and development of potato.…”
Section: Productivity and Soluble Solids Contentsmentioning
confidence: 99%
“…Nevertheless, research on ecophysiological responses of potato cultivars in the tropical Andes is limited. These types of studies and results can be better used as indicators of sustainability of potato farming systems, in which the reduction and substitution of mineral fertilizers by organic fertilizers may be possible to maintain or increase yield (Tiemens-Hulscher et al, 2014, Ohamed et al, 2017.…”
Section: Nitrogen Partitioningmentioning
confidence: 99%
“…The N effect on tuber yield has been well demonstrated (Alva et al, 2002;Maltas et al, 2018). Howe-ver, the potato growth response depends largely on the nitrogen availability in the soil, which may have a considerable effect on the partitioning of assimilates and nitrogen to the different plant organs (Silva et al, 2013;Goméz et al, 2017;Ohamed et al, 2017). This balance of the distribution of biomass and nitrogen to the different compartment may have significant effects on tuber production (Machado & Sarmiento, 2012;Silva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, los factores NO3 -/aniones y K + /cationes afectaron (p≤ 0.05) el índice de cosecha (IC) (Cuadro 9). Las relaciones 60 y 80/100 NO3 -/aniones en la SN redujeron significativamente el IC comparado con la relación 40/100 NO3 -/aniones, atribuido a un retraso en la formación del tubérculo y a una disminución en su crecimiento (Allison et al, 2001), provocado por una elevada fertilización nitrogenada (Vos, 1997), lo que redujo la translocación de C a las hojas y tubérculos y aumentó el flujo de este elemento a las hojas jóvenes, en lugar de los tubérculos (Mohamed et al, 2017). Con las relaciones 35 y 55/100 K + /cationes se obtuvieron los mayores IC (0.4 y 0.38), mientras que el menor IC (0.3) fue obtenido con 15/100 K + /cationes, lo cual implica que las plantas desarrolladas con 35 y 55/100 K + /cationes en la SN destinaron una mayor proporción de asimilados al tubérculo, lo que coincide con Singh y Lal (2012).…”
Section: Resultados Y Discusiónunclassified